(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research article provides a comprehensive analysis of the transformative impact of e-commerce on logistics and supply chain management. In a rapidly evolving digital landscape, traditional supply chain models are undergoing significant changes, prompting an exploration of current trends that shape the future of this industry. The objectives of this study are to highlight key areas of e-commerce influence and to analyze the challenges and opportunities arising from the globalization of e-commerce on cross-border logistics. Employing an analytical research methodology, combining qualitative and quantitative approaches, primary data from a survey of 50 companies and secondary data from literature reviews, research papers, and case studies are integrated to ensure a thorough investigation. The results and discussions focus on the profound impact of e-commerce on order fulfillment, last-mile delivery, inventory management, technology integration, and customer expectations. The study concludes by emphasizing the need for businesses to adapt to these transformative changes, leveraging innovations and reimagining strategies to meet the evolving demands of online consumers.